HUBUNGAN ANTARA MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM (IPA) DI SMP NEGERI 7 KUPANG TIMUR TAHUN AJARAN 2023/2024 - Vivi Seblisa Y. Abamat (SINERGI : Jurnal Riset Ilmiah, 2026)
This study, conducted in February of the 2024/2025 academic year, aimed to determine the relationship between learning motivation and student learning outcomes in science at SMP Negeri 7 Kupang Timur in the 2023/2024 academic year. The population of this study was all 29 seventh-grade students at SMP Negeri 7 Kupang Timur. The sampling technique used was non-probability sampling, thus selecting all seventh-grade students as the sample. Based on the research results and the discussion in the previous chapter, the researcher concluded that there is a very strong relationship between student learning motivation and science learning outcomes in eighth-grade students at SMP Negeri 7 Kupang Timur, with a correlation value of 0.994. This indicates a very strong correlation between variables X and Y. The contribution of variable X to Y is 98.8%, while 1.2% is influenced by other factors such as environmental factors, learning environment, family, and emotional factors.